ATP during Early Bladder Stretch Is Important for Urgency in Detrusor Overactivity Patients. (27th May 2014) - Cheng, Y.; Mansfield, K. J.; Allen, W.; Chess-Williams, R.; Burcher, E.; Moore, K. H.
Abstract : ATP is an important mediator of urgency in women with detrusor overactivity (DO). In order to understand how different degrees of bladder stretch elicited ATP release in DO patients compared with controls, sequential aliquots were collected during cystometry and ATP release was measured at each degree of bladder filling, in female patients with DO and controls. In both DO and control groups, ATP release was induced during bladder filling, suggesting that stretch stimulated further ATP release. However, the luminal ATP concentrations were already high at early filling stage (200 mL), which was even greater than those at the later filling stages (400 mL and maximum cystometric capacity, MCC), indicating that a substantial ATP release has been induced during early filling (200 mL) in both DO and controls. In DO, ATP release at 200 mL was significantly higher in those with low first desire to void (FDV) (≤200 mL) than in those with higher FDV (>200 mL); this may suggest that ATP release at early stretch may play an important role in urgency (early sensation) in DO. ATP concentrations remained unchanged after voiding, suggesting that voiding did not further induce ATP release into intraluminal fluid.